APPLICATION OF MENTORING STRATEGY FOR REDUCING MALE DROPOUT IN SECONDARY SCHOOLS IN ENUGU STATE - Chime, Ngozi Lynda; Ibe, Chima, Emmanuel (Journal of Continuing and Development Education, 2024)
The purpose of the study was to determine the extent to which mentoring strategy is applied in reducing male dropout in secondary schools in the six Education Zones of Enugu State. One research question and two null hypotheses were formulated and tested at .05 level of significance. Descriptive survey research design was adopted for the study. The population for the study comprised all the 335 (295 and 40) secondary school principals in the public secondary schools and Science Technical, and Vocational schools respectively in Enugu State under the control of PPSMB and STVSMB. It is made up of 175 female 160 male principals in the 273 rural and 62 urban public secondary schools in Enugu State. A structured questionnaire was used for data collection. The instrument was validated by three research experts. Cronbach Alpha Reliability Coefficient was used to determine the internal consistency of the instrument. The instrument yielded a reliability coefficient of .69, indicating that the instrument is reliable and suitable for the study. The questionnaire was administered and retrieved by the researcher with the help of six research assistants. Out of the 335 copies of the administered instrument, only 318 copies were retrieved while 17 copies were not retrieved. Data collected with the questionnaire were analyzed using Mean (x̅) with Standard Deviation (SD) to answer the four-research question. However, the hypotheses were tested using t-test statistics at .05 level of significance. Real limit of the mean scores was applied for the decision rule. The null hypotheses were rejected when the significant level was more than .05 and were not rejected when the significant level was equal or less than .05 level of significance. From the result of the findings, it was concluded that; to a great extent mentoring strategy is applied in reducing male dropout in secondary schools in the six Education Zones of Enugu State. Comparison of male and female principals showed that, there was no significant difference in the mean response scores of male and female principals on the extent to which mentoring strategy is applied in reducing male dropout in secondary schools in the six Education Zones of Enugu State, while, there is no significant difference in the mean response scores of urban and rural principals on the extent to which mentoring strategy is applied in reducing male dropout in secondary schools in the six Education Zones of Enugu State. The researcher recommended among others that; mentoring strategy should be strengthened both at the urban and rural secondary schools in the six Education Zones of Enugu State.